ORGANIZATIONAL CULTURE AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: THE MEDIATION ROLE OF ORGANIZATIONAL COMMITMENT - Jufrizen; Azila (RADJA PUBLIKA, 2023)
The purpose of this study was to determine the effect of organizational culture on organizational commitment, the effect of job satisfaction on organizational commitment, the influence of organizational culture on Organizational Citizenship Behavior, the effect of job satisfaction on Organizational Citizenship Behavior, the influence of organizational commitment on Organizational Citizenship Behavior, the influence of organizational culture on Organizational Citizenship Behavior mediated by organizational commitment, and the effect of job satisfaction on Organizational Citizenship Behavior is mediated by organizational commitment to the employees of PDAM Tirtanadi, North Sumatra. The approach used in this study is an associative approach and the population in this study are all employees of PDAM Tirtanadi, North Sumatra. While the samples that met the sampling criteria, the withdrawal of observations was made amounted to 81 people using the Slovin formula. The data collection technique in this study used a questionnaire technique. Data analysis techniques in this study use Partial Least Square (PLS) and Hypothesis Testing. Data processing in this study using the SmartPLS 3.0 software program. The results show that organizational culture affects organizational commitment, job satisfaction affects organizational commitment, organizational culture affects organization citizenship behavior (OCB), job satisfaction affects organization citizenship behavior (OCB), and organizational commitment affects organization citizenship behavior (OCB). , organizational culture affects organizational citizenship behavior (OCB) mediated by organizational commitment, and job satisfaction affects organizational citizenship behavior (OCB) mediated by organizational commitment at PDAM Tirtanadi North Sumatra.